183k views
1 vote
Question from quadratic equation .
solve.
(x-3)(x+7)=0


2 Answers

1 vote

Answer:

3 or -7

Explanation:

For it to equal 0, x must be 3 or -7 because anything multiplied by 0 is 0. So you take each part, x-3 and see how you can make that a 0. x-3=0, therefore x must be 3. Other part x+7=0, x must be -7.

User Matt Whitehead
by
5.0k points
0 votes

Answer:

x = 3, -7

Explanation:

Since you already have the factored form, all you need to do is set the equations equal to zero to find you roots:

x - 3 = 0

x + 7 = 0

x = 3, -7

User Danyamachine
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.